Reasonable opportunity of being heard under article 135(2) of the federal constitution: A mist of obscurity - Abdul Majid Tahir, Mohamed; Zukiferee, Ibrahim (2019)
Article 135(2) of the Federal Constitution provides a right to be heard to any public servants in case of dismissal or reduction in rank by adopting the term ‘reasonable opportunity of being heard’. Meanwhile, the Privy Council in Najar Singh’s case in 1976 established a principle that the right to be heard under Article 135(2) does not imply the right to be heard orally. Despite this precedent, the term remains contentious in the courts of law as to whether the term includes the right to oral hearing. Recently, in 2018 the Federal Court in Vijayaroa’s case inclines in favour of affording a right to be heard orally to an officer facing disciplinary proceedings. This article examined the scope of the term ‘reasonable opportunity of being heard' under Article 135(2) and analysed the development of the cases law on the right to an oral hearing in disciplinary proceedings against public servants. The finding shows that the statutory term ‘reasonable opportunity of being heard’ has been interpreted inconsistently by the courts. Thus, the law on this issue remains unsettled.